A Meta-Analysis: Correlation between Hypertension of Comorbidity on Mortality in Patients with COVID-19 - Nanda Agustian Simatupang; Vitri Widyaningsih; Sumardiyono Sumardiyono (Masters Program in Public Health, 2021)
Background: SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. In severe cases of COVID-19 it can cause pneumonia, acute respiratory syndrome, kidney failure, and even death. Hypertension causes a number of pathophysiological changes in the cardiovascular system such as left ventricular hypertrophy and fibrosis. This can make a hypertensive heart particularly vulnerable to SARS-CoV-2. This study aims to analyze and estimate the effect of comorbid hypertension on mortality in COVID-19 patients.Subjects and Method: This was a systematic review and meta-analysis conducted with PRISMA flow diagram. Article searches through journal databases include: Google Scholar, PubMed, Science Direct, and Springer Link by selecting articles published in 2020 and 2021. The keywords used are “Hypertension” OR “Hypertensive Patient” OR “Blood Pressure”, “Systolic Pressure” OR “Diastolic Pressure” AND “Mortality”, OR “death” OR “loss” AND “COVID-19” OR “SARS-COV-2” OR “coronavirus” AND “multivariate”. The inclusion criteria were full paper articles with observational research methods, the results of the analysis used the aOR value, the exposure given was comorbid hypertension, the research subjects were COVID-19 patients, with mortality outcomes. Eligible articles were analyzed using the Revman 5.3 app. Results: A meta-analysis of 18 articles showed that confirmed COVID-19 patients who had comorbid hypertension had a 1.27 times risk of mortality compared to those without comorbid hypertension and were statistically significant (aOR= 1.27; 95% CI= 1.14 to 1.41; p <0.001).Conclusion: Comorbid Hypertension affects the mortality of COVID-19 patients.